1978
DOI: 10.1021/ja00486a029
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of metal-to-metal multiple bonds. 4. .mu.-Acetylene-bis(cyclopentadienyl)tetracarbonyldimolybdenum compounds. Preparations, properties, structural characterizations, and dynamical solution behavior

Abstract: Cp2Mo2(CO)4, which contains a Mo-Mo triple bond, reacts with acetylenes RC=CR' in hydrocarbon solvents to form 1:1 adducts Cp2Mo2(CO)4(RCCR') in which the acetylenic moiety RCCR', acting as a four-electron donor ligand, bridges two molybdenum atoms that are also joined by a Mo-Mo single bond. The reactivity order HC=CH > MeC=CMe ~PhC=CH > CF3C=CH > CF3C=CCF3 ~PhC=CPh has been found for 1:1 adduct formation. Three of the Cp2Mo2(CO)4(RCCR) compounds, where R = H, Et, and Ph, have been structurally characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
1
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(80 citation statements)
references
References 10 publications
9
69
1
1
Order By: Relevance
“…The lengthening of the C-C bond indicates some reduction in bond order, and this is consistent with the observed decrease of v(C-C) from 1642 to 1592 cm -1 in the infrared spectra of (CsHs)2Rh2(CO)2(CF3C2CF 3) and (CsHs)2Rh2(CO)(CF3C 2CF3), respectively. The average C-C-CF 3 angle of 137.1 (6) is similar to the corresponding angle in related alkyne-dimetal complexes, including 141.3 for Rh2(PF3)4(PPh3)2(PhC2Ph) (Bennett, Johnson, Robertson, Turney & Whimp, 1976) and 134.2 (6) ° for (CsHs)2Mo2(CO)4(EtC2Et) (Bailey, Chisholm, Cotton & Rankel, 1978). The corresponding angle in (CsHs)2RhE(CO)2(CF3C2CF3) is 128.5 (1.0) ° which is closer to the normal olefinic angle of 120 °.…”
Section: Resultssupporting
confidence: 66%
“…The lengthening of the C-C bond indicates some reduction in bond order, and this is consistent with the observed decrease of v(C-C) from 1642 to 1592 cm -1 in the infrared spectra of (CsHs)2Rh2(CO)2(CF3C2CF 3) and (CsHs)2Rh2(CO)(CF3C 2CF3), respectively. The average C-C-CF 3 angle of 137.1 (6) is similar to the corresponding angle in related alkyne-dimetal complexes, including 141.3 for Rh2(PF3)4(PPh3)2(PhC2Ph) (Bennett, Johnson, Robertson, Turney & Whimp, 1976) and 134.2 (6) ° for (CsHs)2Mo2(CO)4(EtC2Et) (Bailey, Chisholm, Cotton & Rankel, 1978). The corresponding angle in (CsHs)2RhE(CO)2(CF3C2CF3) is 128.5 (1.0) ° which is closer to the normal olefinic angle of 120 °.…”
Section: Resultssupporting
confidence: 66%
“…The calculations of the energy barriers for these two processes revealed that (i) the most favored rotamer does indeed possess the C, geometry found crystallographically for Cp,Mo,(CO),As, by Sullivan and Rheingold (30), and (ii) the proposed C,, structure 16, is almost certainly not attainable since it would bring the hydrogens of the cyclopentadienyl groups into direct contact. As Cotton and co-workers have noted (26), these steric constraints are the probable cause of the low symmetry observed even in the parent cluster Cp,Mo,(CO),(HC=CH).…”
Section: (Ch)mo(co) Rotation In [(Ch)mo(co)]cr Clustersmentioning
confidence: 92%
“…The lower energy process involved a pairwise interchange of a terminal carbonyl ligand environment on one molybdenum with a semi-bridging CO on the other metal. The second, and higher energy, process equilibrated the environments of the two cyclopentadienyl groups by a mechanism that must involve some degree of CpMo(CO), vertex rotation (26). It is this latter phenomenon that we wish to address.…”
Section: (Ch)mo(co) Rotation In [(Ch)mo(co)]cr Clustersmentioning
confidence: 98%
See 1 more Smart Citation
“…The molecular structures and fluxional behavior of clusters of the type C~,(CO),M,(R~~%CR~), where M = Mo or W, were first described by Cotton and co-workers (15). In the solid state, three of the carbonyl ligands are terminally bonded while the fourth is in a semi-bridging environment.…”
Section: Resultsmentioning
confidence: 99%